2002
DOI: 10.1046/j.1365-2125.2002.01614.x
|View full text |Cite
|
Sign up to set email alerts
|

The influence of CYP2B6, CYP2C9 and CYP2D6 genotypes on the formation of the potent antioestrogen Z‐4‐hydroxy‐tamoxifen in human liver

Abstract: Aims To investigate in a large panel of 50 human liver samples the contribution of CYP2C9, CYP2D6, and CYP3A4 to the overall formation of the potent antioestrogen Z-4-hydroxy-tamoxifen, and how various genotypes affect its formation from tamoxifen.Methods The formation of Z-4-hydroxy-tamoxifen from 10 mM tamoxifen was studied in human liver microsomes (n=50), characterized for CYP2B6, CYP2C9, CYP2D6 and CYP3A4 expression, and CYP2B6, CYP2C9 and CYP2D6 genotype. The effect of chemical and monoclonal antibody in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
121
0
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(126 citation statements)
references
References 24 publications
3
121
0
1
Order By: Relevance
“…The SSRIs are twice as effective as the "placebo" effect at reducing menopausal symptoms in randomized clinical trials [138][139][140], so there is naturally an increased usage of SSRIs with long-term tamoxifen treatment to maintain compliance. Unfortunately, the metabolism of tamoxifen to hydroxylated metabolites [141][142][143] and the metabolism of SSRIs [39,[144][145][146][147] both occur via the CYP2D6 gene product. Indeed Stearns and coworkers [97] showed that the SSRI inhibitor paroxetine reduced the levels of endoxifen during adjuvant tamoxifen therapy and endoxifen levels decrease by 64% in women with wild type CYP2D6 enzyme.…”
Section: Tamoxifen Metabolism Todaymentioning
confidence: 99%
“…The SSRIs are twice as effective as the "placebo" effect at reducing menopausal symptoms in randomized clinical trials [138][139][140], so there is naturally an increased usage of SSRIs with long-term tamoxifen treatment to maintain compliance. Unfortunately, the metabolism of tamoxifen to hydroxylated metabolites [141][142][143] and the metabolism of SSRIs [39,[144][145][146][147] both occur via the CYP2D6 gene product. Indeed Stearns and coworkers [97] showed that the SSRI inhibitor paroxetine reduced the levels of endoxifen during adjuvant tamoxifen therapy and endoxifen levels decrease by 64% in women with wild type CYP2D6 enzyme.…”
Section: Tamoxifen Metabolism Todaymentioning
confidence: 99%
“…Individual human liver microsome samples were also obtained from a tissue bank, as detailed elsewhere 37 and the CYP2C9 genotyping of these samples was determined as described previously. 38 The distribution of the CYP2C9 genotypes in our panel of 39 individual human liver microsome samples is listed in Table 2.…”
Section: Methodsmentioning
confidence: 99%
“…While tamoxifen-treated women with 2 The International Journal of Biostatistics, Vol. 8 [2012] (Stearns et al, 2003;Coller et al, 2002;Gjerde et al, 2008;Jin et al, 2005), it is also possible that women with two functional CYP2D6*4 alleles may carry other non-functional mutations that reduce the concentration of these metabolites. From a genetic epidemiology perspective, the problem involves non-differential misclassification of metabolizer phenotype because the classification system relies on only one of the alleles with functional consequences.…”
Section: Example 1: Cyp2d6 Function and Tamoxifen Effectiveness Motivmentioning
confidence: 99%
“…Accurate markers of tamoxifen resistant tumors would allow personalization of combined therapies (Riggins et al, 2007), with the goal of preventing these recurrences. Tamoxifen is metabolized mostly by the gene product of CYP2D6 (Stearns et al, 2003;Coller et al, 2002) to secondary metabolites that bind the estrogen receptor 100-fold more readily than tamoxifen itself (Desta et al, 2004), so they are the most important inhibitors of tumor cell growth (Lim et al, 2005). In the past five years, it has been suggested that ER+ breast cancer patients with nonfunctional alleles of CYP2D6 may be poor candidates for adjuvant tamoxifen therapy (Desta and Flockhart, 2007;Jordan, 2007).…”
Section: Example 1: Cyp2d6 Function and Tamoxifen Effectiveness Motivmentioning
confidence: 99%